Tourism Marketing in Bangladesh: What, Why and How - Al- Masud, Tarafder Md. Mehedi (Asian Business Review, 2015)
Bangladesh is a fresh tourism destination. She  has  a vast  prospective  to  develop  tourism  primarily because  of  its  attractive unadulterated natural beauty, heroic historical background and archeological resources, which can be experienced all throughout the land. Tourism sector can play positive impact towards enhancing Gross Domestic Product (GDP).Many countries are now dependent on this sector for foreign currency earnings. Every destination country is trying to achieve more gain by developing this industry. The expansion of the tourism throughout the world has increased. Countries are trying to attract more tourists by adopting appropriate marketing techniques and strategies. A research revealed that the country has a positive trend in arrivals and earnings, and it can be increased to a significant level if the country can undertake appropriate promotion measures by increasing the allocation for this purpose. The country also needs to employ creative people for this purpose, and the quality of the promotional materials also needs to be developed. The paper has been undertaken to investigate how the use of promotional activities can help to develop the tourism industry by giving a special concentration in the case of Bangladesh by observing the current scenario, opportunity, and challenges. The study has intended to evaluate the effective & sustainable tourism marketing for this country.
Keywords: Tourism; GDP; Foreign Currency; Budget; Opportunities; Challenges; Marketing Plans; Marketing Promotions